Political and Judicial Checks on Corruption: Evidence from American State Governments - James E. Alt; David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
The paper investigates the effects of checks and balances on corruption. Within a presidential system, effective separation of powers is achieved under divided government, with the executive and legislative branches being controlled by different political parties. When government is unified, no effective separation exists even within a presidential system, but, we argue, can be partially restored by having an accountable judiciary. Our empirical findings show that divided government and elected, rather than appointed, state supreme court judges are associated with lower corruption and, furthermore, that the effect of an accountable judiciary is stronger under unified government, where government cannot control itself. The effect of an accountable judiciary seems to be driven primarily by judges chosen through direct elections, rather than those exposed to a retention vote following appointment.
Keywords: D72; D73; P48; 330; separation of powers; corruption; rent seeking; checks and balances; political institutions; judicial independence; rule of law; Gewaltenteilung; Korruption; Rent-Seeking; Rechtsstaat; USA; Justiz